The effectiveness of using Powtoon-based learning videos on the learning outcomes of grade XI science students at MAN Sidenreng Rappang - Nur Aisyah; Syamsunir Syamsunir; Muhammad Takdir (Edumaspul: Jurnal Pendidikan, 2025)
This study uses a quantitative method that aims to test whether Powtoon-based learning videos are effective on the learning outcomes of natural science students of Class XI IPA MAN Sidenreng Rappang. The population is 124 students, so the sampling in this thesis is taking all samples if the number of subjects is less than 100, and taking 10-25% of the subjects, or 20-25% of them if there are more than 100 subjects. Because there are only 26 people in the population-total less than 100, the researcher chose to take samples from the entire group using Suharsimi Arikunto's opinion with a sampling technique, namely simple random sampling. There are 2 research variables, namely the independent variable based on Powtoon (X) and the dependent variable, namely the learning outcomes of natural science (Y). This research was conducted at MAN Sidenreng Rappang, precisely in Baranti, Baranti District, Sidenreng Rappang Regency. Data collection techniques using tests and documentation. The collected test data were analyzed using statistical techniques using the mean formula. Based on the results of data analysis, the value of X = 87.17> Y = 40.39 was obtained so that it can be concluded that this study shows the effectiveness of the use of Powtoon-based learning videos on the learning outcomes of natural science students of class XI IPA MAN Sidenreng Rappang. Based on the research results obtained, it can be concluded that the effectiveness of using Powtoon-based learning videos on the learning outcomes of natural science students of class XI IPA MAN Sidenreng Rappang, this shows that the working hypothesis stating that the use of Powtoon-based learning videos is effective in improving the learning outcomes of natural science students of class XI IPA MAN Sidenreng Rappang, is accepted.